A Review of Heat and Mass Transfer in Heat Exchangers - Vimal Sagar,; Versha Joshi,; Rajesh Ranjan,; Manoj Kumar Mishra, (AG Volumes, 2022)
This study provides a comprehensive overview of how heat exchangers may be used to improve heat transmission. Many advantages may be gained by using Process Integration to improve heat transmission. As a first advantage, improved heat exchangers have smaller heat transfer areas for the same heat duty. Second, the size of a particular heat exchanger doesn't have to be raised to enhance the capacity for heat transmission. In this study, we provide a number of strategies for improving the efficiency of shell-and-tube and compact heat exchangers. The techniques take into account the exchanger's initial performance, the amount of surplus pressure drop capacity in the system, the assessment of fouling factors, the usage of augmented surfaces, and the improvement of heat transfer. The heat transfer an energy efficiency of heat exchangers are two areas where nanofluids show tremendous promise for future development. Finally, the geometries tube inserts, baffles, tube deformation, and fins might improve are addressed.